Hospital Management and Nurse Roles: A Case Study on Patient-Centred Care as a Key Driver of Efficiency at XYZ Hospital in Jakarta - Haryanti, Elizabeth; Antonio, Ferdi (Jurnal Manajemen, 2025)
This research investigates the influence of nurses' roles and responsibilities on hospital operational efficiency and the provision of quality care, emphasizing patient centred care as a crucial fac-tor. The study was conducted at a Type C private hospital in Jakarta, with data gathered from 208 nurses possessing over one year of experience. The analysis was performed using SmartPLS®4. The findings reveal that enhancing patient safety, employing evidence-based practice, fostering patient centred care, exhibiting positive interpersonal behaviour, and implementing clinical governance significantly improve hospital operational efficiency. Furthermore, cognitive empathy was found to moderate the effects of evidence-based practice and patient-centred care on operational efficiency, exhibiting both positive and negative impacts. The research indicates that hospital operational efficiency strongly affects the quality of care, with higher nurse perceptions being associated with better quality outcomes. The model demonstrated moderate to strong explanatory power and substantial predictive relevance, underscoring its efficacy in elucidating and forecasting quality care delivery through hospital operational efficiency. These findings underscore the necessity of integrating patient centred care and cognitive empathy into nursing practices to enhance hospital efficiency and the quality of care provided.